Malay parents' considerations when choosing primary schools for their children - Kampulin, Diana Joan (Universiti Malaysia Sarawak, UNIMAS, 2009)
A central concern in the school choice debate is whether parents choose schools based on school quality or any other reasons. In the Western countries, relatively few studies addressing school choice certainly suggest that parents care about academic performance and school status in terms of culture or race. However, literature in Asian countries on parents considerations in making school choice are rather scarce. Thus, this study aimed to investigate parents’ considerations when choosing primary school for their children. Four types of primary schools in Kuching district were selected namely fully-funded schools, missionary schools, Chinese medium schools, and private schools. The study also sought to examine the similarities and differences in the considerations of parents sending their children to various types of schools. A total of 32 participants with 8 parents from each type of school were involved in this study. Data were gathered through extensive semistructured interviews. The findings show there were six major considerations taken by the respondents in choosing primary school for their children. They are convenience, school’s reputation, teachers’ reputation, influence of relatives and/or friends, personal experience, and language related. The study found that convenience was given top priority in choosing primary school for the children but not for private schools parents. Besides, school reputation found to be one of priority for parents from various types of school. Most of the parents also being influenced by their relatives, friends as well as their personal experience when it coming to make a school choice. On the other hand, half of respondents from Chinese medium schools chose the school for the medium of instruction used in the school. On the whole, the study has able to shed a light on importance considerations which influenced parents school choice and hopefully will give significant insight for the educators especially school administrators.